Design of Airscrew Propeller as an Alternative Main Propulsion for Wing in Surface Effect (WiSE) A2C Using the Simplified Method Approach - Sasmito, Cahyo; Pujiwat, Rutma; Priatno, Dany Hendrik; Iskendar, Iskendar; Khoirudin, Muh Hisyam; Eskayudha, Dimas Bahtera (Universitas Sebelas Maret, 2024)
This study focused on developing an airscrew propeller as an alternative propulsion system for the Wing in Surface Effect (WiSE) A2C, employing a rigorous and systematic scientific approach. The design and calculation methodology were grounded in the